International legal content and significance of the Convention on the legal status of the Caspian sea of August 12, 2018 - Rustam F. Mammadov (Проблемы постсоветского пространства, 2019)
The article analyzes the provisions of the new Convention on the legal status of theCaspian sea in 2018.It shows all the new novels, which are the fruit of more than 20 negotiationsof representatives of the presidents of the Caspian States. The article identifies all the positive aspects of the Convention, as well as its shortcomings. The author, in General, positively assessedthe efforts of the Caspian States to coordinate the «Constitution» of the Caspian sea, indicatedthat its adoption will have a charitable value in the life of the States surrounding the Caspian sea.